2020
DOI: 10.1016/j.isci.2020.101161
|View full text |Cite
|
Sign up to set email alerts
|

Time-Restricted Eating: Benefits, Mechanisms, and Challenges in Translation

Abstract: Eating out of phase with daily circadian rhythms induces metabolic desynchrony in peripheral metabolic organs and may increase chronic disease risk. Timerestricted eating (TRE) is a dietary approach that consolidates all calorie intake to 6-to 10-h periods during the active phase of the day, without necessarily altering diet quality and quantity. TRE reduces body weight, improves glucose tolerance, protects from hepatosteatosis, increases metabolic flexibility, reduces atherogenic lipids and blood pressure, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
112
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 134 publications
(119 citation statements)
references
References 85 publications
(140 reference statements)
4
112
0
3
Order By: Relevance
“…Furthermore, improvements in FBG were larger in individuals at risk for developing type 2 diabetes (FBG of at least 100 mg/dl). Although earlier studies on TRE have observed mixed effects on glucose and insulin sensitivity 3 , our data are consistent with more recent studies demonstrating that TRE improves glucose tolerance and insulin sensitivity, especially in individuals with greater cardiometabolic risk 3 , 13 , 27 . Fat mass, blood pressure, and lipids were not measured in this study because they posed additional logistical hurdles for a virtual study.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Furthermore, improvements in FBG were larger in individuals at risk for developing type 2 diabetes (FBG of at least 100 mg/dl). Although earlier studies on TRE have observed mixed effects on glucose and insulin sensitivity 3 , our data are consistent with more recent studies demonstrating that TRE improves glucose tolerance and insulin sensitivity, especially in individuals with greater cardiometabolic risk 3 , 13 , 27 . Fat mass, blood pressure, and lipids were not measured in this study because they posed additional logistical hurdles for a virtual study.…”
Section: Discussionsupporting
confidence: 92%
“…Preclinical studies demonstrate clear beneficial effects of TRE on glucose tolerance and insulin sensitivity, lipid metabolism, obesity, and the gut microbiome 19 . The benefits of TRE on body weight and cardiometabolic markers in humans have only recently been investigated, and most clinical trials of TRE in adults with obesity are of limited sample size and duration 3 , 5 , 15 , 19 , 20 , 22 26 . However, the majority demonstrate that, particularly in individuals with obesity, TRE produces weight loss and enhancements in cardiometabolic health, although the degree of improvements varies across studies and is likely influenced by differences in study population and design.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations